The Vegetative Receptor-Vascular Reflex (VRVR) – A New Key to Regeneration - Ofner, Michael; Walach, Harald (Frontiers in Physiology, 2020)
Objective We describe a potentially new physiological reflex path that has so far been neglected but which could be used for a novel therapeutic approach: The vegetative receptor-vascular reflex. This is a physiological response that starts from the connective tissue and influences the whole organism. We cross-fertilized various research areas with each other. Key Findings The matrix or the connective tissue forms a passive reservoir of substrate for the growth and development of cells, and functions as the primordial communication system of all living systems. It contains a continuous network of cells, such as fibroblasts, along with protein bundles made up of collagen that support electrical exchange through piezoelectrical effects. This archaic vegetative system surrounds all cells, including neurons, and can thus be viewed as the primordial coordinating system in every organism. It is very likely the basis for a reflex which we describe here for the first time: the vegetative receptor vascular reflex. We also indicate some potential practical applications and test procedures. Conclusions The vegetative receptor vascular reflex describes the pathway from stimuli that originate in the connective tissue or the extracellular matrix towards organ systems. They might be chemical in nature or electrical via piezo-electric effects stimulating nerve endings, and thus can influence higher order processes such as regeneration or healing of tissue. Thus, this reflex lends itself to a novel therapeutic approach via certain types of manipulation of the connective tissue.